A prospective study of dietary polyunsaturated fatty acids intake and lung cancer risk. Issue 9 (7th August 2018) - Luu, Hung. N.; Cai, Hui; Murff, Harvey J.; Xiang, Yong‐Bing; Cai, Qiuyin; Li, Honglan; Gao, Jing; Yang, Gong; Lan, Qing; Gao, Yu‐Tang; Zheng, Wei; Shu, Xiao‐Ou
Abstract : Animal studies have shown that polyunsaturated fatty acids (PUFAs) have antineoplastic and anti‐inflammatory properties. Results from epidemiologic studies on specific types of PUFAs for lung cancer risk, however, are inconclusive. We prospectively evaluated the association of specific types of dietary PUFA intakes and lung cancer risk in two population‐based cohort studies, the Shanghai Women's Health Study (SWHS) and Shanghai Men's Health Study (SMHS) with a total of 121, 970 study participants (i.e., 65, 076 women and 56, 894 men). Dietary fatty acid intakes were derived from data collected at the baseline using validated food frequency questionnaires (FFQs). Cox proportional hazards model was performed to assess the association between PUFAs and lung cancer risk. Total, saturated and monounsaturated fatty acid intakes were not significantly associated with lung cancer risk. Total PUFAs intake was inversely associated with lung cancer risk [HRs and respective 95% CIs for quintiles 2–5 vs quintile 1: 0.84 (0.71–0.98), 0.97 (0.83–1.13), 0.86 (0.74–1.01) and 0.85 (0.73–1.00), p trend  = 0.11]. However, DHA intake was positively associated with lung cancer risk [HRs and 95% CIs: 1.01 (0.86–1.19), 1.20 (1.03–1.41), 1.21 (1.03–1.42) and 1.24 (1.05–1.47), p trend  = 0.001]. The ratio of n‐6 PUFAs to n‐3 PUFAs (i.e., 7:1) was inversely associated with lung cancer risk, particularly among never‐smokers and adenocarcinoma patients. Total PUFAs and the ratio between n‐6 PUFAs and n‐3 PUFAs were inversely associated with lung cancer risk. This study highlights an important public health impact of PUFA intakes toward intervention/prevention programs of lung cancer. Abstract : What's new? Polyunsaturated fats have shown anti‐inflammatory and anti‐neoplastic activity. Here, the authors investigated whether eating polyunsaturated fatty acids (PUFAs) affects the risk of lung cancer. Using data from two population‐based cohort studies, the authors evaluated the impact of various dietary fats on lung cancer risk. Total fat, saturated fat and monounsaturated fat consumption showed no association with lung cancer risk. But risk decreased as PUFA intake increased. When they looked at the data on individual fatty acids, though, they found that higher intake of DHA, a component of fish oil supplements, correlated with higher lung cancer risk.